2013
DOI: 10.1371/journal.pone.0081711
|View full text |Cite
|
Sign up to set email alerts
|

RGMa Regulates Cortical Interneuron Migration and Differentiation

Abstract: The etiology of neuropsychiatric disorders, including schizophrenia and autism, has been linked to a failure to establish the intricate neural network comprising excitatory pyramidal and inhibitory interneurons during neocortex development. A large proportion of cortical inhibitory interneurons originate in the medial ganglionic eminence (MGE) of the ventral telencephalon and then migrate through the ventral subventricular zone, across the corticostriatal junction, into the embryonic cortex. Successful navigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 77 publications
4
19
0
Order By: Relevance
“…Previous studies have shown that RGMa‐Neogenin interactions induce embryonic neurogenesis and that RGMa promotes differentiation by potentiating interneuron neurite outgrowth . Our data show that Neogenin activity is required by neuroblasts constrained within the glial tubes of the RMS.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Previous studies have shown that RGMa‐Neogenin interactions induce embryonic neurogenesis and that RGMa promotes differentiation by potentiating interneuron neurite outgrowth . Our data show that Neogenin activity is required by neuroblasts constrained within the glial tubes of the RMS.…”
Section: Discussionsupporting
confidence: 59%
“…RGMa may also act as a guidance cue for migrating neuroblasts. RGMa has been shown to induce a chemorepulsive response in newborn cortical interneurons . Intriguingly, this response was abrogated in the presence of Netrin‐1, suggesting that these ligands may compete for Neogenin binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neogenin is an axon guidance receptor for both Netrin-1 and the repulsive guidance molecules (RGMs) and also regulates neurogenesis, neuronal migration, and neural regeneration (Kam et al, 2016;O'Leary et al, 2013O'Leary et al, , 2015Rajagopalan et al, 2004;Siebold et al, 2017;van Erp et al, 2015). In the early neural tube, Neogenin is required for the establishment of neuroepithelial adhesion and apicobasal polarity (Kee et al, 2008(Kee et al, , 2013Mawdsley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Members of three different families of molecules, namely the netrins, the repulsive guidance molecules (RGMs) and the bone morphogenetic proteins (BMPs), have been reported to bind to neogenin (Hagihara et al, 2011;Rajagopalan et al, 2004;Srinivasan et al, 2003;Wang et al, 1999). RGMs are GPIanchored proteins widely expressed in the nervous system that can repel axons in a neogenin-dependent fashion (Conrad et al, 2010;Monnier et al, 2002;Oldekamp et al, 2004;O'Leary et al, 2013;Rajagopalan et al, 2004;Tassew et al, 2012;Wilson and Key, 2006). Furthermore, RGM-neogenin signaling has been implicated in the regulation of neuronal differentiation, neural tube closure and neuronal survival (Kee et al, 2008;Koeberle et al, 2010;Matsunaga et al, 2006Matsunaga et al, , 2004O'Leary et al, 2015;Shin and Wilson, 2008).…”
Section: Introductionmentioning
confidence: 99%